Analisis Faktor Penentu Optimalisasi Kinerja dan Pelayanan PTN BLU di Universitas Jambi - Wijaya, Rico; Yetti, Susfa; Tiswiyanti, Wiwik (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to analyze the factors that determine the optimization of performance and services of State Universities with Public Service Agency status (Perguruan Tinggi Negeri Badan Layanan Umum or PTN BLU) at Universitas Jambi using the Balanced Scorecard (BSC) approach. The Balanced Scorecard is used as a strategic performance measurement tool by considering four main perspectives: financial perspective, customer perspective, internal business process perspective, and learning & growth perspective. This research employs a descriptive quantitative method to explain the factors contributing to the optimization of performance and services. Data is collected through published financial reports and questionnaires distributed to management, lecturers, students, and academic staff at Universitas Jambi. The findings indicate that the financial perspective, customer perspective, internal business process perspective, and learning & growth perspective play significant roles in enhancing the performance and services of PTN BLU at Universitas Jambi. By understanding these determining factors, Universitas Jambi can formulate more effective strategic policies to improve the performance and services of PTN BLU. The implications of this study are expected to serve as a reference for other universities in implementing the Balanced Scorecard to optimize institutional governance in a more structured and sustainable manner.